Development Of Load Control Algorithm For PV Microgrid - Fatheli, Mohamad Haireen; Zolkifri, Nur Izzati; Gan, Chin Kim; Yusup Lada, Musa (Institute Of Advanced Engineering And Science (IAES), 2017)
The variability of solar irradiance caused by weather conditions could result in the mismatch between the solar PV generation and demand, particularly in the microgrid context. This may lead to detrimental effects of over/under voltage or over/under frequency. In this regard, this paper presents the laboratory setup of a grid-connected PV inverter operating in islanding condition. To achieve this, a load control algorithm is proposed to provide autonomous real time demand control that follows the PV generation to maintain generation-demand equilibrium requirement. Laboratory results show that the proposed load control algorithm is capable to address the voltage and the frequency violation in islanding condition, regardless of the variation of irradiance and power generated by the PV sources.